Semarang City Government Policy on Medical Waste Management of Dental Clinics and Independent Practicing Dentists - Pascalin Fiestarika Indraswari; C. Tjahjono Kuntjoro; Yovita Indrayati (Soepra: Jurnal Hukum Kesehatan, 2021)
Abstract: The number of dental clinics and dentist independent practices in Semarang city has increased every year. This also increases the potential production of the dental health care waste. They could potentially harm the health care personnel, patients, and also the environment because of their harzardous nature. Therefore, Semarang City Government’s role in regulating and making policies is crucial. This study will not just analyze Semarang City Government policies in managing health care waste in dental clinics and independent dentist practices, but also identify the factors that support or inhibit the implementations.